2018
DOI: 10.1002/chem.201704158
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Effects and Stabilization of the Metallic 1T Phase in Layered V‐, Nb‐, and Ta‐Doped WSe2 for Electrocatalysis

Abstract: Layered transition-metal dichalcogenides (TMDs) are valued for their electrocatalytic properties toward the hydrogen-evolution reaction (HER) and oxygen-reduction reaction (ORR). One effective strategy to activate the electrocatalytic properties of TMDs is through doping. The optimistic outlook of doped-MoS as an electrocatalyst witnessed in previous reports spurred us to examine the effect of doping WSe with Group 5 transition-metal species, namely V, Nb, and Ta, in aspects of inherent electroactivities and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…[ 65 ] By doping WSe 2 with transition metals such as V, Nb, Ta, or Cr, the stable 2H phase transforms into the 1T phase. [ 66 ] It was also reported that the doping of semiconducting WS 2 with Ta and Nb produces 1T phase (>50%). [ 67 ]…”
Section: Approaches For 2d Tmd Phase Engineering By Cvdmentioning
confidence: 99%
“…[ 65 ] By doping WSe 2 with transition metals such as V, Nb, Ta, or Cr, the stable 2H phase transforms into the 1T phase. [ 66 ] It was also reported that the doping of semiconducting WS 2 with Ta and Nb produces 1T phase (>50%). [ 67 ]…”
Section: Approaches For 2d Tmd Phase Engineering By Cvdmentioning
confidence: 99%
“…Specifically, there are two main strategies for metallic group VIB TMDs to improve HER performances: doping (or intercalation) and composite structure design. Some atoms such as group V transition metals (V, Nb, and Ta), [276] Sn, [277] N, and P, [278] are proven to be beneficial for different reasons. The introduction of transition metals and Sn could not only stabilize the metastable phase via electron donations, but also enhance the integral conductivity which is largely contributed to the electron transfer in Volmer and Heyrovsky steps.…”
Section: Electrocatalytic Hydrogen Evolution Reactionmentioning
confidence: 99%
“…For instance, studies have reported that when TMDs are doped with metallic heteroatom, their differential free energy of hydrogen adsorption, Δ G H get altered and proton‐transfer kinetics were accelerated, which are beneficial for hydrogen evolution reaction (HER). [ 30–35 ] Doping of TMDs with vanadium (V) reportedly improves the electrical properties of Group 6 TMDs as it changes the semiconducting behaviors to semimetallic, enhance electrical conductivity, and increase carrier concentrations. [ 24,36–38 ]…”
Section: Introductionmentioning
confidence: 99%